Long-term observations of atmospheric CO2 and carbon isotopes at continental sites in Germany - Levin, Ingeborg; Graul, Rolf; Trivett, Neil (Universitätsbibliothek der Universität Heidelberg, 1995)
A network for regional atmospheric CO2 observations had already been established in Germany by 1972, consisting of 5 stations with basically different characteristics: Westerland, a coastal station at the North Sea, 2 regional stations, Waldhof and Deuselbach, as well as 2 mountain stations, Brotjacklriegel at the eastern border of Germany and Schauinsland in the Black Forest. In addition to CO2 concentration observations, from 1977 onwards quasi-continuous 13CO2 and 14CO2 measurements were performed on samples from the Schauinsland site, and for the short period 1985-1988, 14CO2 measurements were also made on Westerland samples. CO2 data selection based on wind velocity allows for an estimate of the representative continental CO2 level over Europe. The peak-to-peak amplitude of the seasonal cycles and the German sites is shifted if compared to maritime background sites with the concentration maxima occuring already between beginning of February and beginning of April, the minima in August. The long-term mean CO2 increase rate in the last 20 years at Westerland and Schauinsland is 1.49 and 1.48 ppmv yr-1, respectively. The mean delta13C of the seasonal source CO2 at Schauinsland is calculated from unselected delta13C and CO2 data to be -25.1 permil. From the 14C observations in unselected CO2, we derive yearly mean fossil fuel contributions at Westerland of 4 ppmv, and at Schauinsland of only 2.5 ppmv. Based on the sesonality of the fossil fuel CO2 component at Schauinsland and on concurrently observed atmospheric 222Radon activities, we derive a seasonal amplitude of the fossil fuel CO2 source which is higher by a factor of 3 compared to emission estimates for Europe.
Wissenschaftl. Aufsatz. - Aus: Tellus B (1995), 47B
Im Titel ist die Zahl 2 tiefgestellt